Responsible research and innovation of carbon removal: strategies for field trials - Waller, Laurie; Cox, Emily; Binner, Amy; Garcia, Tatiana Cantillo; Everett, Rosie; Henwood, Karen; Ingram, Julie; Morris, Carol; O'Sullivan, Kate; Pidgeon, Nick; Price, Catherine; Reed, Mark; et al. (Frontiers in Climate, 2025)
Demonstrating methods for removing carbon dioxide from the atmosphere is now a focus of research and development programmes designed to support decision making about future technology deployment. In this perspective piece, we outline some of the approaches to responsible research and innovation (RRI) being put to work in a United Kingdom-based programme organising field trials of various carbon removal methods. Unlike the disruptive technologies that predominate in RRI scholarship, many land-based methods for carbon removal have already been deployed, in some cases over many decades, with governance closely linked with longstanding fields of research and practice. We highlight why responsible innovation frameworks that developed in the context of geoengineering controversies may be only partially-suited to field trials of land-based carbon removal methods. We suggest that field trials of carbon removal methods are not simply evidentiary procedures but also strategic sites within an emerging innovation regime where RRI approaches can be both implemented and critically tested.